Pharmacokinetics of Tilmicosin in Pigeons, an explorative study - Al-Jumaili, Mustafa A.; Al-Ani, Khudhair A. M. Abed (Revista de Ciências Agroveterinárias, 2025)
Tilmicosin is a semisynthetic macrolide used in the veterinary field to treat various infections caused by gram-positive and gram-negative bacteria in different species. Therefore, this work focused on exploring the single and multiple pharmacokinetics of orally administered Tilmicosin in pigeons, as there is limited information available on this topic. For this study, six pigeons weighing about 0.35 kg were used as model; a single oral dose of Tilmicosin (15 mg/kg) was administered every 24 hours for three consecutive days. The microbiological assay was applied to measure plasma concentrations of Tilmicosin. The non-compartmental analysis revealed that the highest measured concentration was 0.258 μg/ml two hours after administration, the area under the curve was 2.119 μg/ml.h, the area under the moment curve was 36.069 μg/ml.h2, the mean residence time was 13.893 hours, the half-life was 11 hours, and the terminal elimination rate constant was 0.063 h-1. The pharmacokinetics of multiple doses of Tilmicosin showed that the estimated time to reach the steady state was 44 hours, the ratio of accumulation was 1.283, the remnant fraction was 0.22 μg/ml, and the total area under the curves was 8.77 μg/ml·h. The maximal, trough, and average concentrations at steady state were 0.331 μg/mL, 0.073 μg/mL, and 0.202 μg/mL, respectively. The study concluded that the pharmacokinetics of Tilmicosin in different administration patterns could provide sufficient tissue concentrations, influencing the contact time with tissue-invading bacteria in a manner similar to that observed in other animal species. This could qualify Tilmicosin as a viable option for the treatment of many bacterial diseases in pigeons.